EFEKTIVITAS PEMBERIAN JUS TOMAT TERHADAP PENURUNAN KADAR KOLESTEROL DARAH PADA TIKUS PUTIH YANG DIINDUKSI DIET TINGGI LEMAK - SADILA KELIAT; HUWAINAN NISA NASUTION (LP2MTBM MAKARIOZ, 2023)
Heart and blood vessel disease is one of cause of death in the world with unhealthy lifestyle that increase total cholesterollevels. Tomato juice (Lycopersacum esculentum M.) contains lycopene which has high antioxidant so that it can decreasecholesterol levels. The type of research is experimental using pretest posttest design with control group design that use 24male white rats (Rattus norvegicus L. wistar strain induced by 6.25g/kgBW egg yolk, grouped into 4, the negative controlgroup was given with standard feeding, the positive control group was given quail egg yolk, the 1st treatment grup was givenwith 11ml/kgBW tomato juice and the 2nd treatment group was given with 30ml/kgBB tomato juice on 3 cc for 2 weeks, andthen the blood was measurement for 2 times, with pretest and posttest. The results of the Repeated ANOVA test showed asignificant difference between the pretest-posttest on the 1st treatment group and the 2nd treatment group. There was asignificant difference in the mean total of cholesterol level before and after treatment (p<0.05) in the positive control group(p=0.001), in the 1st treatment group (p=0.001) and the 2nd treatment group (p=0.000). While the mean total of cholesterolbetween the 1st treatment group and the 2nd treatment group had a difference with p value = 0.000 (p <0.05).The conclusionsare There was an effectiveness of giving tomato juice to reduce blood cholesterol in white rats that have been induced by ahigh-fat diet, where the administration of tomato juice at 30 ml/kgBW is more effective in reducing the average of cholesterollevel.